Integrated pest management tactics and predatory coccinellids: A review - Ahmed, Kanwer Shahzad; Majeed, Muhammad Zeeshan (published online, 2016)
Integrated pest management, defined as an approach in comprehensive meaning by the selection, integration and implementation of sustainable pest control tools to keep pest status to endurable levels while maintaining a quality environment and mankind health. Why we need IPM? Utilization of chemicals as one and only choice for eradication of pest problems has been enormously criticized due to many reasons. For instance, negative impact of these pesticides on non-target organisms including natural predators and parasitoids of different insect pests, their high toxicity to environment and human beings and the rapid development of pesticide resistance in insect pests and disease pathogens are the most peculiar scenarios. A careful implementation of an IPM strategy is the only solution for alleviating these negative impacts of pesticides on environment and predatory ladybird beetles (Coleoptera: Coccinellidae) hold the premise for an increased reliability of biological control of insect pests and a successful integration of integrated pest management.
full text
Keywords: IPM, Coccinellid beetles, Predator-Prey Relation, Cultural Control, Chemical Control, Biological Control